Pengaruh Circuit Training Terhadap Kekuatan Fisik Pada Atlet Sekolah Sepakbola (SSB) Persisac Semarang - Umar Fitriadi Umar Fitriadi (Journal of Physical Activity and Sports (JPAS), 2021)
Circuit Training is a form of training in which there are various movements that are carried out together and continuously and are limited by rest at each exchange of training forms with circuit training there will be many positive shifts in basic skills and also simultaneously restore physical fitness, muscle ability, endurance, dexterity and flexibility of the body. Strength needs to be given special attention from the coach so that the achievements of the SSB (Football School) Persisac Semarang do not decline. The research used in this study is "One-Groups Pretest-Posttest Design". The sample in this study was football athletes SSB Persisac Semarang. The sampling technique was purposive sampling of 15 players. Retrieval of data using instruments that have been used, with the pre-test and post test. Based on the results of the t test, the t value (31.281)> t table (1.761) was obtained, and the p value <0.05. This result means that Ho is accepted, so the hypothesis states that there is an effect of Circuit Training training on increasing the physical strength of football school students at SSB Persisac Semarang.